2015
DOI: 10.1186/s12943-015-0415-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anti-tumour biologics using primary tumour models, 3-D phenotypic screening and image-based multi-parametric profiling

Abstract: BackgroundMonolayer cultures of immortalised cell lines are a popular screening tool for novel anti-cancer therapeutics, but these methods can be a poor surrogate for disease states, and there is a need for drug screening platforms which are more predictive of clinical outcome. In this study, we describe a phenotypic antibody screen using three-dimensional cultures of primary cells, and image-based multi-parametric profiling in PC-3 cells, to identify anti-cancer biologics against new therapeutic targets.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…41,42 The induction of apoptosis in the presence of extracellular matrix components, collagen I and Matrigel (collagen IV, laminin, enactin/nidogen-1 and proteoglycans), may indicate that ECC inhibits stellate structure formation, which is indicative of cell binding and anchoring to these substrates during invasion. This explanation is supported by a study showing preferential and direct binding of β 1 integrin to cCDCP1 over flCDCP1.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The induction of apoptosis in the presence of extracellular matrix components, collagen I and Matrigel (collagen IV, laminin, enactin/nidogen-1 and proteoglycans), may indicate that ECC inhibits stellate structure formation, which is indicative of cell binding and anchoring to these substrates during invasion. This explanation is supported by a study showing preferential and direct binding of β 1 integrin to cCDCP1 over flCDCP1.…”
Section: Discussionmentioning
confidence: 99%
“…Executing this approach requires a characteristic phenotype associated with the disease that is known. Cell-based phenotypic assays usually use primary cells [11], isolated pathogens [12], engineered cell lines [13] or the recently emerged iPSC-derived cells including neuronal cells, cardiomyocytes, hepatocytes and epithelial cells [1416]. As an example of this, Eggan, Woolf and co-workers discovered hyperexcitability as a result of a reduced delayed-rectifier potassium channel as a disease phenotype in iPSC-derived motor neurons from amyotrophic lateral sclerosis (ALS) patients [16].…”
Section: Phenotypic Screening Assaysmentioning
confidence: 99%
“…We have also demonstrated that phage display may have advantages over hybridoma-based screening, due to the ability to rationally deselect antibodies to known or abundant antigens, therefore enabling access to wider pools of targets during the screening process [17, 18]. …”
Section: Introductionmentioning
confidence: 99%